COP28 and environmental federalism: Empirical evidence from an emerging economy, India - Lekha Chakraborty; Amandeep Kaur; Ranjan Kumar Mohanty; Divy Rangan; Sanjana Das (Levy Economics Institute of Bard College, 2024)
Against the backdrop of COP28, this paper investigates the impact of intergovernmental fiscal transfers (IGFT) on climate change commitments in India. Within the analytical framework of environmental federalism, we tested the evidence for the Environmental Kuznets Curve (EKC) using a panel model covering 27 Indian States from 2003 to 2020. The results suggest a positive and significant relationship between IGFT and the net forest cover (NFC) across Indian states. The analysis also suggests an inverse-U relationship between Gross State Domestic Product (GSDP) and the environmental quality, indicating a potential EKC for India. The findings substantiate the fiscal policy impacts for climate change commitments within the fiscal federal frameworks of India, and the significance of IGFT in increasing the forest cover in India. This has policy implications for the Sixteenth Finance Commission of India in integrating a climate change-related criterion in the tax-transfer formula in a sustainable manner.
Keywords: E6; H5; H7; 330; Environmental Federalism; Environmental Kuznets Curve; Intergovernmental Fiscal Transfers; Government Expenditures